Treatment of Intracranial Aneurysms Using the New Silk Vista Flow Diverter: Safety Outcomes at Short-Term Follow-Up - Pumar, José M.; Mosqueira, Antonio; Olier, Jorge; Rodriguez-Fernandez, Claudio; Vega, Pedro; Gonzalez-Diaz, Eva (Frontiers in Neurology, 2021)
Background: Flow diverters are widely used as the first endovascular treatment option for complex brain aneurysms due to their high percentage of occlusion and low morbi-mortality. The Silk Vista device is a new generation of flow diverters designed to facilitate full visibility, improve apposition to the vessel wall, and enhance navigability. Indeed, its greatest advantage is that it enables the easier navigation of stents between 3.5 and 4.75 mm through a 0.021 microcatheter. The objective of this study was to evaluate the safety and effectiveness of Silk Vista systems for treating cerebral aneurysms. Methods: This prospective observational study included 25 consecutive patients with 27 wide-necked unruptured aneurysms treated with SILK Vista who were retrospectively analyzed for safety and efficacy. Results: Endovascular treatment was successfully performed in all patients. The final morbidity and mortality rates were both 0.0%. Short-term (3–5 months) angiographic follow-up revealed 21 complete occlusions and 6 near-complete occlusions. No significant parent artery stenosis was observed. Conclusions: This report demonstrates the efficacy of Silk Vista in treating brain aneurysms, although longer experiences should be carried out to confirm our results.